How can high-quality development improve the ecotourism efficiency in the region of ecological constraints of China? Empirical evidence from the Yellow River Basin - Hao, Junqing; Guo, Ying; Wu, Mengyao; Luo, Zhixin (Frontiers in Ecology and Evolution, 2023)
Despite the massive impacts of ecotourism on regional development, only limited papers empirically examined the responses of regional development factors to ecotourism in the context of an ecological constraints region. To fill this gap, the primary aim of this paper is to reveal how ecotourism efficiency is affected by quality regional development in the region of ecological constraints. The second aim is to investigate the moderating role of ecological constraints in building relationships of ecotourism efficiency and quality regional development factors. The research was conducted in the Yellow River Basin, a prime area for ecological protection and High-quality regional development in China. Data gathered from 2010 to 2019 were used to analyse ecotourism efficiency by using the Super-SBM method. Findings indicated that four quality regional development factors-innovative, green, open and shared factors-have positive impacts on ecotourism efficiency in the Yellow River Basin. Ecological constraints moderate the relationship between ecotourism efficiency and quality regional development. The study makes a significant contribution to the literature in terms of both managing the ecological constraints and improving the sustainability of ecotourism in the region of quality development.